Development of a NeuroNICU with a Broader Focus on All Newborns at Risk of Brain Injury: The First 2 Years - Van Meurs, Krisa P.; Yan, Elisabeth S.; Randall, Kathi S.; Chock, Valerie Y.; Davis, Alexis S.; Glennon, Cecelia S.; Clark, Catherine L.; Wusthoff, Courtney J.; Bonifacio, Sonia L. (American Journal of Perinatology, 2018)
Objective Many critically ill neonates have an existing brain injury or are at risk of neurologic injury. We developed a “NeuroNICU” (neurologic neonatal intensive care unit) to better provide neurologically focused intensive care.Study Design Demographic and clinical variables, services delivered, and patient outcomes were recorded in a prospective database for all neonates admitted to the NeuroNICU between April 23, 2013, and June 25, 2015.Results In total, 546 neonates were admitted to the NeuroNICU representing 32% of all NICU admissions. The most common admission diagnoses were congenital heart disease (30%), extreme prematurity (18%), seizures (10%), and hypoxic–ischemic encephalopathy (9%). Neuromonitoring was common, with near-infrared spectroscopy used in 69%, amplitude-integrated electroencephalography (EEG) in 45%, and continuous video EEG in 35%. Overall, 43% received neurology or neurosurgery consultation. Death prior to hospital discharge occurred in 11%. Among survivors, 87% were referred for developmental follow-up, and among those with a primary neurologic diagnosis 57% were referred for neurology or neurosurgical follow-up.Conclusion The NeuroNICU-admitted newborns with or at risk of brain injury comprise a high percentage of NICU volume; 38% had primary neurologic diagnoses, whereas 62% had medical diagnoses. We found many opportunities to provide brain focused intensive care, impacting a substantial proportion of newborns in our NICU.
Keywords: neuroNICU; neuromonitoring; neurocritical care; seizure; cEEG; aEEG